Effect of alcoholic extract of soy bean consumption by pregnant mice on the testis and epididymis of their male offspring's - Abeer Salih Ali; Nisreen Khazal Flayyih; Hadeel Mohammed Qasim (College of Pharmacy / Mustansiriyah University, 2013)
Soy is flavones are phytoestrogens with potential hormonal activity due to their similar chemical structure to 17-B-estradiol. The increasing availability of Soy is flavones throughout the food supply and through use of supplements has prompted extensive research on biological benefits to humans in chronic disease prevention and health maintenance. The objective of this study was to assess the effect of consumption of soy bean by pregnant mice on histomorphology of testis, epididymis in the male offspring's. Twenty pregnant female mice at age of six weeks were used as a model for this study. After 40 days (around the puberty age) the animals were sacrificed to get their testes and epididymis each testis and epididymis was weighted, then prepared using routine histological technique mouse born from mother treated with Soy bean extract (1.5mg daily), Note the absence of mature sperms and the appearance of immature sperms in the lumen seminiferous tubules and the appearance immature sperms connected to the germinal epithelium, and also we note in the epididymis of young male mouse from mother treated with soy bean extract absence of mature sperms in the lumen of the epididymis. Diameters of seminiferous tubules and epididymis together with the thickness of their germinal wall were calculated, these observation indicate that the perinatal exposure of male mice to is flavones affected in testies and epididymis, and they imply that Soy bean has potential implication for testis function.